CHARACTERIZATION ANALYSIS OF THE MAIN CHARACTER OF THE SECRET GARDEN (A Comparative Study of Characterization in the Movie and Novel) - Arif - Hidayat; Clara Dita Septi Wulansari (LPPM Universitas Bina Sarana Informatika, 2016)
The purpose of this research is to analyze the characterization of the main character in novel and movie of The Secret Garden. In this research, the writers use descriptive qualitative research with comparative study to analyze the characterization of the main character, Mary Lennox, in the novel and movie The Secret Garden. From the comparative analysis of the characterization of the main character in novel and movie The Secret Garden, it is found that, in the novel, the method that is used to reveal and develop Mary Lennox’s character is direct characterization, which is done through the appearance, the author, through the dialogue, and the action. Meanwhile, there are transformation of the characterization through some reduction and addition to the characterization of the main character. Beside the difference of the method of characterization used, it is also found that there are some differences of the representation of Mary Lennox’s character between the novel and the movie. Keywords: Characterization, Novel, Movie